A novel method to design Nb(W)–Ti–Co(Fe) alloy membrane with high hydrogen permeability and strong resistance to hydrogen embrittlement - Kunjun Zhu; Quan Zhang; Xinzhong Li; Zhaoxiang Ma; Xiangjin Zhao; Zhongli Liu; Jingjie Guo (Journal of Materials Research and Technology, 2023)
A hydrogen permeable Nb43W5Ti27Co20Fe5 alloy membrane was designed and its microstructure and hydrogen transportation performances were systematically studied. W mainly dissolves into primary body-centered cubic (bcc)-(Nb) phases, while Fe is captured in eutectic structures. Substituting Nb with W leads to a substantial reduction in hydrogen solubility and substituting Co with Fe negligibly affects hydrogen solubility. The W and Fe substitutions contribute to an enhanced intrinsic hydrogen diffusion coefficient D∗. The designed Nb43W5Ti27Co20Fe5 alloy membrane exhibits lower hydrogen solubility and higher hydrogen permeability at temperatures below 623 K than that of the original Nb48Ti27Co25 alloy membrane. No hydrogen-induced failures were found for the designed Nb43W5Ti27Co20Fe5 alloy membrane during cooling to room temperature and under long-term hydrogen permeation at 673 K for 72 h, whereas the original alloy membrane failed at 444 K during cooling to room temperature and after 19 h during hydrogen permeation at 673 K. The designed Nb43W5Ti27Co20Fe5 alloy membrane exhibits high hydrogen permeability and strong resistance to hydrogen embrittlement.